Analysis of Faktor Influecing Emplyment Opportunities in Jambi Province 2014-2023 - Zasriati, Masrida; Putri, Osi Hayuni; Harahap, Erni Febrina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims : 1) To determine the effect of economic growth and the rate of population growth on job opportunities in province Jambi in 2011-2020, partially and simultaneous. 2) To calculate the great effect of economic growth and the rate of population growth for job opportunities in 2011-2020 in province jambi,partially and simultaneous. The data used in this study are secondary data. The method used in this study is multiple linier regression analysis. The result of this study indicate that simultaneously,there is the influence of economic growth and population of the on job opportunities in provinces Jambi province in 2011-2020. From the result of this study,the effect of economic growth and population of population on job opportunities in provinces Jambi in 2011-2020 is 11,4% while the remaining 88,4% are affected by other factors that have not been studied in this study.